The Effect of Wall Pass Exercises and Exercises With Groups of 4 on Passing ResultsPS Undikma Mataram Football in 2024 - Fadli Zainuddin (JOETAL: Journal of Education, Teaching and Learning, 2024)
The focus of this research problem is that mistakes in passing often disrupt concentration and feeling nervous when competing. This results in passes not reaching friends, passing too fast, and passing carelessly so it doesn't match the target. So the 4-1 training model uses two touches and 4-1. The aim of this research is to determine the effect of wall pass training and exercise with groups of 4 on PS Undikma Mataram football passing results in 2024. The research methods used by researchers are the observation method, documentation method and action test method. The research design uses "One-Group Pretest-posttest Design" (initial test and final test). The researchers used the entire population to be used as research samples, namely the entire Undikma PS, totaling 20 active people, where the sample was divided into two, namely 10 players using the 4-1 training model using two and 10 players using the one touch method. The sampling technique uses purposive sampling. From the statistical results above are: seen from the results of research X1 with Y passing wall pass training seen from tcount > ttable (5,162 > 1,833). The influence of wall pass training and exercise with groups of 4 on PS Undikma Mataram football passing results in 2024'. And X2 exercise with groups of 4 with Y passing seen from t-count > t-table (6,867 > 1,833). with Y football passing obtained tcount is much greater than ttable, so it can be concluded that "there is an influence of exercise with groups of 4 on the football passing results of PS Undikma Mataram in 2024." accepted.